PENGARUH PIKIRAN POSITIF TERHADAP KESEHATAN MENTAL: SUATU ANALISIS KONSEPTUAL - Hasan, Maulana; Mud'is, Hasan (FASTABIQ: JURNAL STUDI ISLAM, 2022)
Mental Health is a condition that should be taken care of like keeping the body healthy. This article aims to analyze the relationship between positive thinking and mental health maintenance. The research work carried out follows the conceptual analysis offered by Ludwig Wittgenstein's analytic philosophy. This article concludes that a healthy mind and mental health need to be maintained and harmonized at all times. As with taking care of the body, mental health must also be maintained starting from the way of daily activities and the way of thinking as well. Mental health is much influenced by the work of the brain and the brain certainly needs good nutrition. Through positive thinking to anyone and at any time, it can also make life happy and live with peace that can cause our mental health. Maintaining personal health also depends on the individual itself. So if you feel that something is not okay in you then you have to start doing something, because being happy is a person's choice. Keywords: Mental health, Happy,  Positive Thinking, Brain